East African highland cooking banana: towards an efficient selection of hybrids with user-preferred food quality traits - Nowakunda, K.; Khakasa, E.; Ceballos, H.; Kenneth, A.; Tumuhimbise, Robooni; Bugaud, C.; Asasira, M.; Uwimana, Brigitte; Bouniol, A.; Nuwamanya, E.; Forsythe, L.; Marimo, Pricilla; et al. (Wiley, 2024)
BACKGROUND Determinants of culinary qualities of East African highland cooking bananas (EAHCB) are not well known. This constrains the inclusion of user-preferred traits in breeding. The present study aimed to quantify key indicators of user-preferred characteristics to enable selection of acceptable hybrids.